Effect of treatment technique on radiation exposure in mechanical thrombectomy for acute ischaemic stroke: A matched-pair analysis. Issue 4 (August 2020) - Weyland, Charlotte S; Neuberger, Ulf; Seker, Fatih; Nagel, Simon; Arthur Ringleb, Peter; Möhlenbruch, Markus A; Bendszus, Martin; Pfaff, Johannes AR
Abstract: Objective: This study aimed to compare radiation exposure (RE) in patients receiving mechanical thrombectomy (MT) for large-vessel occlusions in the anterior circulation using direct thrombo-aspiration (DT) versus stent-retriever thrombectomy under continuous distal aspiration (STA). Methods: This was a retrospective single-centre analysis of an Institutional Review Board−approved stroke database of a comprehensive stroke centre focusing on RE per dose area product, procedure time (PT) and fluoroscopy time (FT) in patients receiving MT. Patients who received MT with DT were matched with patients treated using STA according to occlusion location, mode of anaesthesia, manoeuvre count and sex. Results: Apart from patient age (DT: M = 74 years (standard deviation ( SD )=13 years); STA: M = 79 years ( SD = 11 years); p = 0.023), there was no difference in baseline patient characteristics ( n = 68 per group). PT (DT: median = 26 minutes (interquartile range (IQR) = 21–38 minutes); STA: median = 49 minutes (IQR 37–77 minutes); p < 0.0001) and FT (DT: median = 12 minutes (IQR 7–18 minutes); STA: median = 26 minutes (IQR 14–43 minutes); p < 0.0001) were shorter in patients who received MT using DT. RE (DT: median = 62.6 Gy·cm 2 (IQR 41.7–89.4 Gy·cm 2 ); STA: median = 89.8 Gy·cm 2 (IQR 53.7–131.7 Gy·cm 2 ); p = 0.034) was significantly lower in patients who received MT using DT. This represents a relative increase of RE, FT and PT by 43.6%, 116.6% and 88.5%, respectively, in patients who received MT using STA. Conclusion: MT using DT is associated with shorter FT and PT and lower RE compared to matched patients treated with STA.